An ERP Selection Framework in Constructor Companies using Fuzzy AHP Approach - mohammad ali Shahhosseini; Rouhani Rouhani; Rouhi Rouhi (Journal of Information Technology Management)
The success in ERP implementation is definitely based on selecting an appropriate system which is more aligned with enterprise culture, infrastructure and requirements, and that's why ERP selection, the process and impressive criteria have been increasingly attended in recent years. The constructor companies are strongly affected by ERP systems. A successful implementation will improve their productivity and promote their performance considerably. However, it is a challenge for decision-makers to identify the real needs, define the criteria, select the acceptable vendor and purchase the most appropriate system. This study is developed to present a Fuzzy AHP-based framework for selecting ERP systems in constructor companies. In this study, the impressive criteria have been collected by reviewing previous studies and researches, a questionnaire was used to assess and define the criteria and sub-criteria’s priority. Afterward, another questionnaire was used to compare the alternatives regarding to each criteria. Eventually, the Fuzzy Analytic Hierarchical Process was used to select a system which is more aligned with the organization’s requirements and strategies